Solid fuels for cooking and tobacco use and risk of major chronic liver disease mortality: a prospective cohort study of 0.5 million Chinese adults - Chan, K; Bennett, D; Chen, Y; Chen, Z; Lam, K (Oxford University Press, 2019)
Background: Harmful substances in solid fuel and tobacco smoke is believed to enter the bloodstream via inhalation and metabolised in the liver leading to chronic liver damage. However, little is known about the independent and joint effects of solid fuel use and smoking, on risks of chronic liver disease (CLD) mortality. Methods: During 2004-2008, ~0.5 million adults aged 30-79 years were recruited from 10 areas across China. During a 10-year median follow-up, 2461 CLD deaths were recorded. Multivariable Cox regression yielded adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) for the individual associations of self-reported long-term cooking fuel and tobacco use with major CLD death. Results: Overall, 49% reported solid fuel use and 26% smoked regularly. Long-term solid fuel use for cooking and current smoking were associated with higher risks of CLD deaths, with adjusted HRs of 1.26 (95% CI, 1.02-1.56) and 1.28 (1.13-1.44), respectively. Compared to never-smoking clean fuel users, the HRs were 1.41 (1.10-1.82) in never-smoking solid fuel users, 1.55 (1.17-2.06) in regular-smoking clean fuel users and 1.71 (1.32-2.20) in regular-smoking solid fuels users. Individuals who had switched from solid to clean fuels (1.07, 0.90-1.29; median 14 years) and ex-regular smokers who stopped for non-medical reasons (1.16, 0.95-1.43; median 10 years) had no evidence of excess risk of CLD deaths compared to clean fuel users and never-regular smokers, respectively. Conclusion: Among Chinese adults, long-term solid fuel use for cooking and smoking were each independently associated with higher risks of CLD deaths. Individuals who had stopped using solid fuels or smoking had lower risks.